2012
DOI: 10.1159/000342460
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Delayed-Onset Propionibacterium acnes Endophthalmitis after Cataract Surgery with Implantation of a Preloaded Intraocular Lens

Abstract: Purpose: To report a case of delayed-onset endophthalmitis after implantation of a preloaded intraocular lens (IOL) and examine the surgically removed IOL by scanning electron microscopy (SEM). Case: A 77-year-old female underwent uneventful phacoemulsification and aspiration with preloaded silicone IOL implantation. Since intraocular inflammation unexpectedly worsened 1 month after the surgery, she was referred to our hospital. Her visual acuity was hand motion in the left eye. Hypopyon and fibrin formation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…This treatment strategy allows the removal of localized infectious sources while leaving enough capsular support for the IOL(26) . If the conservative-IOL surgical treatment is not e cient, as observed in our case 1, removal of the entire CB and the IOL is required to eradicate all sites of intraocular infection (9,13,15,17,19,23,26,27,34,(43)(44)(45)(46)(47)(48)73,76). Surgical treatments were observed in 50% of this case series, which agrees with other studies that reported it in approximately 30% to 73% of cases (12,15,16,27,41).…”
Section: Discussionmentioning
confidence: 87%
“…This treatment strategy allows the removal of localized infectious sources while leaving enough capsular support for the IOL(26) . If the conservative-IOL surgical treatment is not e cient, as observed in our case 1, removal of the entire CB and the IOL is required to eradicate all sites of intraocular infection (9,13,15,17,19,23,26,27,34,(43)(44)(45)(46)(47)(48)73,76). Surgical treatments were observed in 50% of this case series, which agrees with other studies that reported it in approximately 30% to 73% of cases (12,15,16,27,41).…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, C. acnes resistance to fluoroquinolones develops in an anaerobic environment [ 6 ], and therefore may be promoted by its sequestration within an intracapsular plaque. In addition, biofilm formation by C. acnes confers resistance to antibiotics and promotes the production of virulence factors [ 21 , 22 ]. Interestingly, the antibiotic rifampin is known to improve the penetration of vancomycin through biofilms [ 23 ], and oral rifampin has excellent intraocular penetration in humans [ 24 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Literature has reported delayed onset postoperative infection after the implantation of preloaded IOL [ 12 , 13 ]. However, none of the patients developed postoperative infection in the follow up period of six months.…”
Section: Discussionmentioning
confidence: 99%